Evaluation of Measures of Urinary Albumin Excretion in Epidemiologic Studies - Dyer, Alan R. (Am J Epidemiol, 2004)
Twenty-four-hour urinary albumin excretion (UAE) is considered the gold standard for determining albumin level in epidemiologic studies, but this measure is inconvenient and often unavailable. Simpler alternatives include the albumin:creatinine ratio (ACR) and urinary albumin concentration (UAC) obtained from a single sample. The authors assessed the strengths and weaknesses of ACR and UAC as alternatives to UAE using albumin measurements from two 24-hour urine samples collected in 1996–1999 from 4,678 participants aged 40–59 years in the International Study of Macronutrients and Blood Pressure (17 population samples from four countries). The authors compared ACR and UAC with regard to correlations with UAE, daily within-person variability, and associations with known predictors of UAE. Rank-order correlations of ACR with UAE were 0.949 and 0.942 for men and women, respectively, versus 0.881 and 0.816 for UAC. Mean within-person coefficients of variation were 34.0–40.0% for the three measures, with the smallest values being observed for UAC. Average correlations with blood pressure were similar for UAE, ACR, and UAC, but the correlation with body mass index was lower for ACR (0.118 for ACR and 0.188 for UAC vs. 0.211 for UAE) because of high correlation between body mass index and creatinine level. Thus, UAC and ACR are acceptable alternatives to the more complex UAE, and the simpler UAC may be preferable to ACR in some respects.